2010
DOI: 10.1111/j.1365-2524.2010.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural professionals’ perceptions of interprofessional continuing education in mental health

Abstract: We describe the impact of an interprofessional education programme in mental health for professionals in six rural Canadian communities. The 10-session programme, offered primarily via videoconference, focussed on eight domains of mental health practice. One hundred and twentyfive professionals, representing 15 professions, attended at least some sessions, although attendance was variable. Data were collected between September 2006 and December 2007. The programme was evaluated using a mixed methods approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 26 publications
1
43
0
1
Order By: Relevance
“…MacDonald et al (2008) conducted a study utilizing open-ended questions and prompts and found that learners applied new skills in their practice after completing the described IPE module. Church et al (2010) also observed increases in mental health practitioners' self-reported confidence in interventions and knowledge of mental health issues, suggesting greater awareness about community resources, referrals, and collaborations. Six of the eight (75.0%) studies that reported outcomes at the acquisition of knowledge/skills level (2b) reported positive findings as a result of ICT-mediated IPE using pre-and post-test measures.…”
Section: Level 2b: Acquisition Of Knowledge/skillsmentioning
confidence: 80%
See 1 more Smart Citation
“…MacDonald et al (2008) conducted a study utilizing open-ended questions and prompts and found that learners applied new skills in their practice after completing the described IPE module. Church et al (2010) also observed increases in mental health practitioners' self-reported confidence in interventions and knowledge of mental health issues, suggesting greater awareness about community resources, referrals, and collaborations. Six of the eight (75.0%) studies that reported outcomes at the acquisition of knowledge/skills level (2b) reported positive findings as a result of ICT-mediated IPE using pre-and post-test measures.…”
Section: Level 2b: Acquisition Of Knowledge/skillsmentioning
confidence: 80%
“…In two studies, Careau et al (Careau, Dussault, & Vincent , 2010;Careau et al, 2008) examined the utility of videoconferencing as a method for practitioners to meet and develop interprofessional care plans, noting that the technology could be effectively used to engage community partners and improve team productivity. Church et al (2010) used post-program focus groups and interviews at 6-12 weeks for professionals from 15 health care professions, who participated in a 10-week interprofessional rural mental health program. The authors described that inter-agency linkages, referrals, and consultations had increased noticeably after program participation.…”
Section: Level 4a: Change In Organizational Practicementioning
confidence: 99%
“…These values represent the level of agreement. compared with a mean of 5.0/10 sessions, SD 2.9, for all participants (Church et al, 2010). There were no significant differences in Attitude or Perception change scores or postknowledge scores for community, profession, age or years of experience.…”
Section: Quantitative Perspectivesmentioning
confidence: 84%
“…It was considered innovative in several respects: (a) it was longer than most rural mental health training programs (multiple sessions over approximately 20 weeks); (b) the training comprised both didactic evidence-based mental health intervention material and interactive experiential teaching tools and (c) the program was designed to simultaneously promote skill development in mental health interventions (stages of change model, motivational interviewing, solution-focused therapy, cognitive-behavioral approaches, assertive community treatment and crisis intervention) and increase interprofessional and intersectoral practice (Table I). Some outcomes from the program related to participant satisfaction (Heath et al, 2008) and impact on mental health knowledge and confidence (Church et al, 2010) have already been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Conclusão: a videoconferência foi uma ferramenta válida e aceita pelos profissionais estudados para ser utilizada em programas de capacitação em saúde auditiva infantil. A videoconferência como instrumento frente às atividades de educação permanente em saúde é recente no país [4][5] , mas experiências internacionais acumuladas até o presente momento evidenciaram não somente resultados positivos, com a mudança do comportamento do profissional após a capacitação, como também grande aceitação do recurso tecnológico para estas atividades [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Na Portaria SAS n o .…”
Section: Opinião Dos Agentes Comunitários De Saúde Sobre O Uso Da Vidunclassified